Demobilizing and Reintegrating FARC Fighters: The challenges faced to end the forever war - Christian Vianna de Azevedo (Academia Nacional de Polícia, 2016)
Fuerzas Armadas Revolucionarias de Colombia - FARC has consolidated its position as the longest surviving and the most entrenched guerrilla movement in all of the Americas. FARC has been steadily weakened after significant leadership losses, more than half of its foot soldiers and a substantial amount of its experienced mid level commanders. Yet peace is not in sight. Colombian civil war happens to be the stereotypical intractable conflict. Colombian state forces have been increasingly powerful, yet the guerrilla, although crippled, is entrenched and resilient. The government has relied on the demobilization program as a way out for a conflict that seems ripe for resolution. Colombian demobilization program is called PAHD – Programa de Atención Humanitaria al Desmovilizado. It has been highly regarded and approved by the population and by the demobilized as well. One of the greatest concerns of the government is about the life of the ex-fighters after demobilization. The economic reintegration has proven to be arduous and recidivism may be a problem. Yet there are other concerns about the defeat of FARC that have to be worked together with the demobilization program so peace can be finally achievable.